Effect of tree species diversity on the neuropterid community in a deciduous forest - Gruppe, Axel (Acta entomologica slovenica (Ljubljana), 2011)
The neuropterid communities of a temperate deciduous forest in Gemany were studied using flight-interception traps in the tree crown stratum in the year 2005. In total 884 specimens were captured, representing 23 species of Neuropterida. The communities captured in monospecific beech stands significantly differed from those of more diverse stands. Diversity of Neuropterida was positively correlated with tree species diversity. Abundance of dominant species was either negatively or positively correlated with tree diversity, indicating different levels of host tree association of the particular species.
Keywords: canopy fauna; entomologija; entomology; favna; favna drevesnih krošenj; habitat heterogeneity; habitatna raznolikost; mrežekrilci; neuropterid diversity; Neuropterida; raznolikost drevesnih vrst; raznovrstnost mrežekrilcev; tree species diversity